Políticas de desenvolvimento regional-territorial e governança: uma análise recente sobre o Estado do Maranhão (Brasil) - Carvalho, Fernanda Cunha de [UNESP] (2015)
The related research is concerned with the theme of development, given its importance in the face of geographical analysis (with focus on Economic and Regional Geography) confirming the maintenance of a necessary dialogue with other areas of science. Observation of Maranhão (situated in the context of Brazil and the Northeast) was sent by the thesis that portrays that failure of regional- territorial development in the state, beyond the structuralist elements, must be simultaneously analyzed together with the governance practices, which It has not achieved its operational dimension and disregards the basic principles of a widespread and democratic proposal on an applied development at the local level. Therefore, there was the help of bibliographic references, documentary and cartographic and conducting quantitative research (powered by databases) and qualitative (strengthened by interviews in government institutions). Upon this overview, Maranhão, can be set as a politically and economically, dependent state, the concentration of power and wealth in state figures, large companies and some territories reflected in the indexes data that demonstrate the high degree of inequalities sites. Still, it found certain evolution and expansion in discussions on the development and introduction of the possibility of social participation in political decisions, it is considered a comparison of the government plans and multi-annual plans. However, there has been a more discursive evolution rather than operational, demonstrating the fragility of the governance. The performed approach indicates that it considers to be far from reaching a conclusion about the possibilities surrounding the development in Maranhão, however, to emphasizes the needs, to create strategies that optimize economic growth, but that go beyond this line, which indicates that it should set goals for the territories previously invisible, being the main government interests focuses...